Reply to: Asymptomatic infection by SARS 2 coronavirus: invisible but invincible (2020)
The current literature gives indications of the median duration of virus shedding of 11.5 days for pre-symptomatic, 28 days for asymptomatic and 31 days for mildly symptomatic patients (Li et al. 2020). Another study using the similar gene target ORF1ab as described by Malagón-Rojas et al. shows that median Ct values during hospitalization were significantly higher in asymptomatic patients (39.0, IQR 37.5- 39.5) than in asymptomatic patients during the incubation period (34.5, IQR 32.2- 37.0), indicating a significantly lower viral load (Zhou et al. 2020). Long-term virus shedding was documented rather in asymptomatic than in symptomatic patients and virus shedding did not correspond to viral infectivity (Long et al. 2020)